PENGARUH BAHAN TAMBAHAN ANTI STRIPPING PADA CAMPURAN ASPAL PANAS HOT ROLLED SHEET WEARING COURSE YANG MENGGUNAKAN AGREGAT LOKAL - Bambang Jaya (Jurnal Teknologi Berkelanjutan, 2013)
Road damages commonly found in Indonesia include surface damages that occur too early, as indicated by surface exfoliation, surface rutting, particle discharge and cracks. Based on a laboratory-scaled study at the Road and Bridge Research and Development Center in 2009, local aggregates of Central Kalimantan in Lupu, Runtu and Bukit Sintang quarries generally meet the requirements of road pavement materials. However, as part of asphalt mixtures, these aggregates fail to meet the requirement as they produce only 80percent asphalt-aggrate adhesion, and Marshall’s stability index of 40 percent. Adhesion of up to 95 percent and residual stability index of 90 percent require a particular type of additives. This research was conducted in a laboratory by implementing Marshall method. The objective of this research is to identify the characteristics of surface layers of HRS-WC mixture at optimum bitumen content levels. Shell asphalt was used with a penetration of 60/70, coarse aggregates and fillers (rock ash) from Hampangen, fine aggregates from Tangkiling, and the anti-striping Wetfix Be additive. The results show that for an asphalt concrete surface layer (HRS-WC) withthe addition of Wetfix Be of up to 0.2percenttheoptimum bitumen content is 6.60 percent, with Wetfix Be of 0.4percentthe optimum bitumen content is 6.65 percent, and with Wetfix Be of 0.6 to 0.8percentthe optimum bitumencontent is 6.7 percent. The stability index shows that the higher the of Wetfix Be content is, the lower the stability index will be. The highest stability index,that is 1370 kg, is obtained without any addition of Wetfix Be, while the lowest stability index,namely 1170 kg, is obtained by adding Wetfix Be as much as 0.8 percent of the mixture.A series of void in mixture (VIM) tests without the addition of Wetfix Be resulted in a 3.80-percent absolute density and adding Wetfix Be up to 0.8percentof the mixture resulted in a 3.60-percent absolute density. The result of tests on the HRS-WC durability show that without the addition of Wetfix Be the retained stability index is 86 persent, which does not meet the requirement (that is < 90 percent). Adding Wetfix Be of 0.2 percent increases this index to 91 percent, adding Wetfix Be of 0.4 percent increases this index to 97 percent, and adding Wetfix Be of 0.8 percent increases this index to 95 percent. This suggests that the HRS-WC mixture using local aggregates from Hampangen and Tangkiling sand requires Wetfix Be additive to meet the durability requirements of HRS-WC mixture.